2001
DOI: 10.1029/2000ja000181
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Joule heating in structured electric field environments

Abstract: Abstract. We have recently performed a detailed characterization of ion Joule heating perpendicular to an axial magnetic field in the laboratory in a simulated ionospheric plasma environment which contains localized electric field structuring. Since Joule heating is often regarded as an important mechanism contributing to energization of outflowing heavy ions observed by higher-altitude auroral satellites, this work has particular relevance to space physics issues, and, to our knowledge, has not been investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The standard deviations of the data sets are plotted for each point. Consistent with earlier work [ Walker et al , 2001], the ion temperature tends to reach a maximum at the peak of the Joule heating rate curve which is strongly dependent on the Pedersen conductivity and therefore ν in /Ω i . In the present case, the results shown are for a plasma density of 5 × 10 7 cm −3 and a magnetic field of 40 gauss.…”
Section: Summary Plot Of Ion Temperature Versus Pressuresupporting
confidence: 89%
See 3 more Smart Citations
“…The standard deviations of the data sets are plotted for each point. Consistent with earlier work [ Walker et al , 2001], the ion temperature tends to reach a maximum at the peak of the Joule heating rate curve which is strongly dependent on the Pedersen conductivity and therefore ν in /Ω i . In the present case, the results shown are for a plasma density of 5 × 10 7 cm −3 and a magnetic field of 40 gauss.…”
Section: Summary Plot Of Ion Temperature Versus Pressuresupporting
confidence: 89%
“…In this regard, for example, combined incoherent scatter radar in addition to satellite in situ measurements have unequivocally established that irregular field structures encountered in regions of small convective velocity are associated with ion heating. Earlier laboratory investigations [ Amatucci et al , 1999; Walker et al , 2001] have shown that there are two dominant processes responsible for ion temperature enhancement in the presence of transverse electric fields: (1) Joule, or collisional, heating in regions of high convective velocity and sufficient neutral density and, (2) wave heating via plasma instabilities in the presence of velocity shear. These works demonstrate conclusively the transition between these two forms of heating as a function of plasma neutral density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial production of the field and experimentation however is done in vacuum at pressures near 5 × 10 −5 Torr. Further descriptions of the chamber and diagnostic measurement capability in general may be found elsewhere [ Walker et al , 1997, 2001]. To provide the x‐component of the modified Harris field of , the grid is pulsed and the field component produced by the pulsed grids adds to the constant z‐component produced by the external Helmholtz coils.…”
Section: Experimental Overviewmentioning
confidence: 99%